1999
DOI: 10.1152/ajpgi.1999.277.6.g1200
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide mediates hepatic arterial vascular escape from norepinephrine-induced constriction

Abstract: The involvement of nitric oxide (NO) in the vascular escape from norepinephrine (NE)-induced vasoconstriction was investigated in the hepatic arterial vasculature of anesthetized cats. The hepatic artery was perfused by free blood flow or pump-controlled constant-flow, and NE (0.15 and 0.3 microg x kg(-1) x min(-1), respectively) was infused through the portal vein. In the free-flow perfusion model, the NE-induced hepatic vasoconstriction recovered from the maximum point of the constriction, resulting in 36.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…These results suggest that the 2.5 m g/mL dose of angiotensin II can cause vasoconstriction in the adjacent and distant normal liver that is suffi cient to decrease the BF and BV in these regions without invoking the hepatic arterial buffer response ( 30 ) or inducing hepatic arterial vascular escape ( 31 ), which cause arterial vasodilatation in the normal liver parenchyma that is mediated by increased local levels of adenosine and nitric oxide, respectively. The combination of these two hepatic refl ex responses has been shown to give the normal liver the unique ability to escape from severe vasoconstrictive infl uences ( 30,31 ); this appears to have occurred at the higher angiotensin II doses, especially 50.0 m g/mL, in our study. Furthermore, only at the 2.5 m g/mL dose was the capillary permeabilitysurface area product of the tumor signifi cantly higher than that of the surrounding normal liver tissue.…”
Section: Practical Applicationmentioning
confidence: 96%
“…These results suggest that the 2.5 m g/mL dose of angiotensin II can cause vasoconstriction in the adjacent and distant normal liver that is suffi cient to decrease the BF and BV in these regions without invoking the hepatic arterial buffer response ( 30 ) or inducing hepatic arterial vascular escape ( 31 ), which cause arterial vasodilatation in the normal liver parenchyma that is mediated by increased local levels of adenosine and nitric oxide, respectively. The combination of these two hepatic refl ex responses has been shown to give the normal liver the unique ability to escape from severe vasoconstrictive infl uences ( 30,31 ); this appears to have occurred at the higher angiotensin II doses, especially 50.0 m g/mL, in our study. Furthermore, only at the 2.5 m g/mL dose was the capillary permeabilitysurface area product of the tumor signifi cantly higher than that of the surrounding normal liver tissue.…”
Section: Practical Applicationmentioning
confidence: 96%
“…Other mediators involved in regulatory processes of mesenteric and hepatic blood fl ow are norepinephrine, epinephrine, agents originating from the renin-angiotensin-aldosterone sytem, endothelins and nitric oxide (see Disturbances in mesenteric blood distribution during critical illness below) [47][48][49][50].…”
Section: Regulation Of Hepatic Perfusionmentioning
confidence: 99%
“…Nitric oxide attenuates experimental norepinephrineinduced vasoconstriction [49]. A recent clinical study demonstrated that inhaled nitric oxide reduced reperfusion-induced hepatic cell death and improved liver function tests in patients undergoing liver transplantation [54].…”
Section: Disturbances In Mesenteric Blood Distribution During Criticamentioning
confidence: 99%
“…17 This demonstration of the essential functional role of NO in the regulation of the IHVR was confirmed later in different species and using different experimental approaches. 18,19 Using the classical method of the hepatic venous wedged pressure to measure liver sinusoidal pressure in the isolated perfused liver, we determined that in normal rat liver NO modulates sinusoidal and presinusoidal resistance whereas in the cirrhotic liver NO has a predominant sinusoidal effect. 20,21 Recent studies investigated the enzymatic origin of this NO production in the liver.…”
Section: Mechanisms Of Action In Intrahepaticmentioning
confidence: 99%